Mapping Research Trends in Maritime Education and Training: A Bibliometric Analysis (International Journal of Scientific Research and Management (IJSRM), 2025)
This study aims to analyze current research trends in Maritime Education and Training (MET) and to identify key gaps that warrant further investigation. As the maritime industry undergoes rapid technological and regulatory transformation, there is an increasing need for adaptive and effective educational practices. A bibliometric analysis was conducted using VOSviewer to map and visualize scholarly output on MET published between 2020 and 2024. The analysis examined 471 documents indexed in Scopus that were relevant to the term “Maritime Education and Training.” The study explored connections between keywords, citation behaviors, and thematic clusters to map the intellectual composition of the discipline. The findings reveal that dominant research themes include “education,” “STCW,” “marine industry,” “blended learning,” and “learning system,” indicating a strong emphasis on regulatory compliance and digital learning models. However, critical areas such as active learning methods, simulation-based training, and cyber security remain underrepresented in the existing literature. These gaps indicate that, although foundational elements of MET are well-developed, innovative pedagogical strategies and emerging digital threats remain largely excluded from current maritime curricula. The study highlights the need for future research to explore interactive and technology-enhanced learning approaches that can improve student engagement and operational preparedness.